Arthritis in Kawasaki disease: A poorly recognised manifestation. (26th June 2018) - Martins, Andreia; Conde, Marta; Brito, Maria; Gouveia, Catarina
Abstract : Aim: To determine the prevalence of arthritis in Kawasaki disease (KD) and the clinical characteristics of children with KD and arthritis. Methods: This was a single‐centre, 15‐year, retrospective study of children admitted with KD. Clinical features (including coronary involvement), laboratory results and treatment response were evaluated. Results: Of 63 children with KD, 60.3% were male, with a median of age of 2.0 years. Complete KD was found in 68.3%. The time from symptom onset to treatment was 7.0 days (median); 30.7% had coronary artery aneurysms, from which 82.5% responded to intravenous immunoglobulin. During the course of their illness, eight children developed arthritis (12.7%), which was early onset in six (75%) and oligoarticular in five (62.5%). The median number of joints was 3.5 (P25 = 1.3, P75 = 17.0), and at least one large joint was affected. In all cases, the arthritis was self‐limited and left no sequelae, lasting a median of 14 days and no longer than 22 days. KD children with arthritis were older ( P = 0.025), and those with early‐onset arthritis responded to first‐line therapy, unlike the late‐onset group ( P = 0.018). Conclusions: This study emphasises the value of a systematic articular examination of joints in KD. Refractory KD was observed in children with late‐onset arthritis.